On The Constitutionality And Public Administration In Ancient And Medieval Armenia - Suvaryan, Yuri (ՀՀ ԳԱԱ)
Summing up, it should be noted that the state and regional government in ancient and medieval Armenia was realized via legal regulatory principles, consistent with the time and through sufficient constitutionality. Within the frames of Armenian intellectual culture, certain methodological bases were worked out, whereas the accumulated past experience, cultural heritage and the lessons of history in particular, deserve special attention in terms of the appropriate orientation of the civil society, the development of political thought and growth of efficiency in public administration
Keywords: Demography; Governance